Specialization in volleyball game - Primary and secondary demands from the setter position - Vujmilovic, A.; Karalic, T. (Sports Science and Health, 2013)
In team sports there must be a player specialized in the organization of the games. In volleyball game this role is assigned to the setter. It is not uncommon to hear the claim that the setter is ''the brain in the team''. With that we want to emphasize that the setters are players from which depends overall organization of the game. However, the setter with the prefix ''top'' must meet certain condition: functional, motor abilities and anthropometric or morphological characteristics but also meet certain requirements. The Characteristics of top setter is to be various and unpredictable especially when he set up the ball to attack, so that his every action has a tactical justification and be unexpected for opponents. Primary demands for the setter that he as a specialist must meet are the proper technique for setting a ball, mastering of all kinds of setting techniques, tactical ability of reviews and ability of peripheral vision. Secondary demands that one specialist make complete in this area are mastering of spike techniques in attack and in defense, assuming the role of assistant of end-blocker. How is possible to ''produce'' of such a player, it is hard to say, however, the fact is that in modern volleyball exists positive trend outstanding setters despite the fact that today it is much more difficult to succeed in the struggle for this specific player's position in the team